Pemahaman Mahasiswa Terhadap Pancasila Sebagai Paradigma Dalam Pembangunan Nasional - Dea Fadilla; Nur Hafizah Azzaro; Novita Rahma Yanti; Usiono Usiono (LPPM Politeknik Pratama, 2024)
Pancasila is the basis of the Indonesian state and its ideology which plays an important role in national development. Students' understanding of Pancasila as a national development paradigm is very important to ensure the sustainability of the nation's noble values in all aspects of life. This study aims to analyze students' level of understanding of Pancasila values (Pancasila as a national development paradigm) and how this understanding can be implemented in the context of national development. Through surveys and in-depth interviews, data were obtained from a number of student respondents representing various disciplines.